MyPyramid Message: Proportionality - Claudia Peñuela; Karla P. Shelnutt (EDIS, 2010)
FCS8929, a 2-page handout by Claudia Peñuela and Karla P. Shelnutt, explains how proportionality is represented in the MyPyramid symbol and provides guidelines for practicing proportionality to balance one’s diet. Includes a quiz and references. Published by the UF Department of Family, Youth and Community Sciences, October 2010.